24.6k views
1 vote
Given that f(x)=6x^2-900

User Nebi
by
5.0k points

2 Answers

6 votes
Solution for F(x)=6x^2-900 equation:
Simplifying F(x) = 6x2 + -900 Multiply F * x xF = 6x2 + -900 Reorder the terms: xF = -900 + 6x2 Solving xF = -900 + 6x2 Solving for variable 'x'. Reorder the terms: 900 + xF + -6x2 = -900 + 6x2 + 900 + -6x2 Reorder the terms: 900 + xF + -6x2 = -900 + 900 + 6x2 + -6x2 Combine like terms: -900 + 900 = 0 900 + xF + -6x2 = 0 + 6x2 + -6x2 900 + xF + -6x2 = 6x2 + -6x2 Combine like terms: 6x2 + -6x2 = 0 900 + xF + -6x2 = 0
User Wilkins
by
5.3k points
4 votes

Answer: Its d

Step-by-step explanation: I did the usa test prep

User Abu Saeed
by
5.2k points